West Java Regional Police Public Relations Personnel’s adaptation to digital age communication - Sani, Anwar; Sumartias, Suwandi; Hafiar, Hanny; Ismail, Nurzali (PRofesi Humas, 2022)
The development of communication and information technology supports the use of various media to convey messages or information to the public. Therefore, the National Police of the Republic of Indonesia, as one of the largest institutions in Indonesia, is expected to be proactive in utilizing new media to utilize information. Various new policies will be implemented, including using the NCO as the spearhead of public communication in this digital era. However, these non-commissioned officers are uncomfortable sitting in their position as public relations officers who act as police communicators with digital technology that accompanies their work. This study explores the adaptation process carried out by young non-commissioned officers who manage police communications through social media and the obstacles they face in the adaptation process. To explore these activities, the researchers will use two theories: technological adaptation and the Social Construction of Technology. This research is a case study research with the descriptive data type. Data collection is based on interviews, observation, and also documentation. The results and discussion of this research show that public relations personnel at the West Java Police must adapt because they do not have a qualified educational background in public relations, especially communication in the digital era. SOPs and management for communication depend on what the leader is inclined to do. Public Relations personnel attended training from within the police organization. However, the training cannot improve their abilities in the short term. Ensuring that our Regional Police have SOPs in managing social media and conducting training could be the problem-solving needed.